Life‐long diseases need life‐long treatment: long‐term safety of ciclosporin in canine atopic dermatitis. (1st March 2014) - Nuttall, Tim; Reece, Douglas; Roberts, Elizabeth
Abstract : Ciclosporin (Atopica; Novartis Animal Health) has been licensed for canine atopic dermatitis (AD) since 2002. Adverse events (AEs) have been reported in 55 per cent of 759 dogs in 15 clinical trials, but are rare in pharmacovigilance data (71.81 AEs/million capsules sold). Gastrointestinal reactions were most common, but were mild and rarely required intervention. Other AEs were rare (≤1 per cent in clinical trials; <10/million capsules sold). Hirsutism, gingival hyperplasia and hyperplastic dermatitis were rarely significant and resolved on dose reduction. Ciclosporin decreases staphylococcal and Malassezia infections in AD, and at the recommended dose is not a risk factor for other infections, neoplasia, renal failure or hypertension. The impact on glucose and calcium metabolism is not clinically significant for normal dogs. Concomitant treatment with most drugs is safe. Effects on cytochrome P450 and MDR1 P‐glycoprotein activity may elevate plasma ciclosporin concentrations, but short‐term changes are not clinically significant. Monitoring of complete blood counts, urinalysis or ciclosporin levels is not justified except with higher than recommended doses and/or long‐term concurrent immunosuppressive drugs. Ciclosporin is not a contraindication for killed (including rabies) vaccines, but the licensed recommendation is that live vaccination is avoided during treatment. In conclusion, ciclosporin has a positive risk‐benefit profile for the long‐term management of canine AD.